Evaluation of Antioxidant Potential, Enzyme Inhibition, and Chemical Profiling Through Mass Spectrometry on Bark Extract of Berberis aristata - Bhattarai, Keshab; Pandey, Indira; Sharma, Khaga Raj (Journal of Nepal Chemical Society, 2024)
Berberis aristata, a plant from the Berberidaceae family, is renowned for its medicinal properties. The presence of bioactive metabolites in its bark underscores its importance in traditional medicine and pharmacology. This study primarily focuses on the biological activities of the plant bark extract, specifically its antioxidant properties and alpha-glucosidase inhibition. In addition to these activities, mass spectrometry-based compound annotation was conducted to explore the metabolites present in the plant bark extract. In this study, the bark samples were collected and extracted using the cold percolation method with methanol. Subsequently, an ethyl acetate fraction was obtained from the methanol extract using a separating funnel. The methanol extract of the bark showed a total phenolic content (TPC) of 70.056 ± 2.52 mg GAE/g and a total flavonoid content (TFC) of 11.89 ± 0.16 mg QE/g. To determine the antioxidant activity of the samples, a DPPH assay was used. The ethyl acetate fraction of the bark showed potent antioxidant activity with an IC50 value of 188.93 ± 8.35 μg/mL, while the methanol extract of the bark showed radical scavenging activity with an IC50 value of 242.89 ± 4.62 μg/mL. In terms of alpha-glucosidase inhibition, the methanol extract of the bark had low enzyme inhibition activity, but the ethyl acetate fraction exhibited potential inhibition with an IC50 value of 112.99 ± 10.28 µg/mL. These results indicate that the plant bark extract is rich in phenolic content compared to flavonoid content. Additionally, the ethyl acetate fraction of the plant bark exhibits potent radical scavenging activity and inhibition of the digestive enzyme alpha-glucosidase. Mass spectrometric-based identification of metabolites revealed that the methanol extract of the bark contains compounds such as Palmatin, columbamine, and berberal. The presence of these metabolites further supports the medicinal use of this plant bark. These findings enhance the plant’s potential in the drug discovery process in the future.